2017
DOI: 10.18632/oncotarget.15792
|View full text |Cite
|
Sign up to set email alerts
|

CCDC106 promotes non-small cell lung cancer cell proliferation

Abstract: Coiled-coil domain containing (CCDC) family members enhance tumor cell proliferation, and high CCDC protein levels correlate with unfavorable prognoses. Limited research demonstrated that CCDC106 may promote the degradation of p53/TP53 protein and inhibit its transactivity. The present study demonstrated that CCDC106 expression correlates with advanced TNM stage (P = 0.008), positive regional lymph node metastasis (P < 0.001), and poor overall survival (P < 0.001) in 183 non-small cell lung cancer cases. A549 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 20 publications
0
37
1
Order By: Relevance
“…Accumulating experimental evidence has indicated that CCDC family members have a pivotal role in several processes associated with tumorigenesis and tumor progression . Nonetheless, the expression patterns and functions of CCDC85B in malignancies remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulating experimental evidence has indicated that CCDC family members have a pivotal role in several processes associated with tumorigenesis and tumor progression . Nonetheless, the expression patterns and functions of CCDC85B in malignancies remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating experimental evidence has indicated that CCDC family members have a pivotal role in several processes associated with tumorigenesis and tumor progression. [3][4][5][6] Nonetheless, the expression patterns and functions of CCDC85B in malignancies remain unknown. To the best of our knowledge, this is the first study that investigated the protein expression of CCDC85B and its correlation with the clinicopathological profiles in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, coiled-coil domain containing family members have been associated with tumor cell proliferation. CCDC106 is associated with the progression and poor prognosis of non-small cell lung cancer (10), while CCDC67 has been demonstrated to inhibit the proliferation of papillary thyroid carcinomas (11). A genome-wide association study (GWAS) in China identi ed colorectal cancer risk single nucleotide polymorphism (SNP) rs1076394 as an expression Quantitative Trait Loci (eQTL) for CCDC12 (12).…”
Section: Introductionmentioning
confidence: 99%